Pengaruh perputaran kas dan perputaran piutang terhadap profitabilitas pada PT Tiga Pilar Sejahtera Food Tbk - Aida Kartika Surya; Wardayani Wardayani (Forum Kerjasama Pendidikan Tinggi, 2021)
The purpose of this study was to determine whether there is an effect of cash turnover and accounts receivable turnover on the company's profitability simultaneously and partially at PT.Tiga Pilar Sejahtera Food Tbk for the period 2011-2018. Types and sources of data in this study was secondary data in the form of financial statements of the company PT.Tiga Pilar Sejahtera Food Tbk in 2011-2018. Data analysis used multiple linear regression test, hypothesis testing used the coefficient of determination (R2), simultaneous test (F test) and partial test (t test) with data processing used SPSS statistics 20 program. The results showed that the coefficient of determination test (R2 ) obtained a result of 0.343 or 34.3%, indicating that the cash turnover and accounts receivable turnover variables were able to explain their existence to the profitability variable, while the remaining 65.6% was explained by variables not studied. The results of the study partially showed that cash turnover has no and insignificant effect on profitability, while accounts receivable turnover has a significant and significant effect on profitability. Meanwhile, simultaneously cash turnover and accounts receivable turnover have a positive and significant effect on profitability